RelB+ Steady-State Migratory Dendritic Cells Control the Peripheral Pool of the Natural Foxp3+ Regulatory T Cells - Döhler, Anja; Schneider, Theresa; Eckert, Ina; Ribechini, Eliana; Andreas, Nico; Riemann, Marc; Reizis, Boris; Weih, Falk; Lutz, Manfred B. (Frontiers in Immunology, 2017)
Thymus-derived natural Foxp3+ CD4+ regulatory T cells (nTregs) play a key role in maintaining immune tolerance and preventing autoimmune disease. Several studies indicate that dendritic cells (DCs) are critically involved in the maintenance and proliferation of nTregs. However, the mechanisms how DCs manage to keep the peripheral pool at constant levels remains poorly understood. Here, we describe that the NF-κB/Rel family transcription factor RelB controls the frequencies of steady state migratory DCs (ssmDCs) in peripheral lymph nodes and their numbers control peripheral nTreg homeostasis. DC-specific RelB depletion was investigated in CD11c-Cre x RelBfl/fl mice (RelBDCko), which showed normal frequencies of resident DCs in lymph nodes and spleen while the subsets of CD103- Langerin- dermal DCs (dDCs) and Langerhans cells (LCs) but not CD103+ Langerin+ dDC of the ssmDCs in skin-draining lymph nodes were increased. Enhanced frequencies and proliferation rates were also observed for nTregs and a small population of CD4+ CD44high CD25low memory-like T cells (Tml). Interestingly, only the Tml but not DCs showed an increase of IL-2 producing capacity in lymph nodes of RelBDCko mice. Blocking of IL-2 in vivo reduced the frequency of nTregs but increased the Tml frequencies, followed by a recovery of nTregs. Taken together, by employing RelBDCko mice with increased frequencies of ssmDCs our data indicate a critical role for specific ssmDC subsets for the peripheral nTreg and IL-2+ Tml frequencies during homeostasis.